Diurnal rhythms and obesity. Issue 4 (July 2021) - Paschos, Georgios K.
Abstract : Purpose of review: This review will discuss the recent studies that implicate disturbed diurnal rhythms with the development of obesity. The second part of the review will discuss studies that use feeding time to restore diurnal rhythms and rescue obesity. Recent findings: Studies in patients with obesity and diabetes reveal attenuated circadian and metabolic rhythms in adipose tissue. The use of animal models furthers our mechanistic insight on how environmental disturbances such as high-fat diet and shift work disturb circadian and metabolic rhythms. Studies in both animals and humans describe how disturbance of diurnal rhythms can lead to increased adiposity and obesity. The effects of time-restricted feeding in animals and the time of feeding in humans provide new evidence on how restoring diurnal rhythms can reverse adiposity and obesity. Summary: Many more studies in humans were performed in recent years to confirm a number of findings from animal studies. It is becoming apparent that the time of feeding and maintaining a healthy daily schedule is important for metabolic health. Ongoing studies may soon improve current recommendations regarding the time of eating and time of day behavior.